A comparative study of clonidine and dexmedetomidine as an adjunct to bupivacaine in supraclavicular brachial plexus block - Archana Tripathi; Khushboo Sharma; Mukesh Somvanshi; Rajib Lochan Samal (Wolters Kluwer Medknow Publications, 2016)
Background and Aims: Various additives are mixed with local anesthetic agents to increase the quality of block in regional anesthesia. We compared clonidine and dexmedetomidine as an adjunct to bupivacaine in supraclavicular brachial plexus block with respect to the onset and duration of sensory and motor block and duration of analgesia. Material and Methods: Sixty American Society of Anesthesiologists Grades I and II patients scheduled for various orthopedic surgeries of the upper limb under supraclavicular brachial plexus block were divided into two equal groups in a randomized, double-blind manner. Patients were assigned randomly to one of the two groups. In Group C (n = 30), 39 ml of 0.25% bupivacaine plus 1 ml (1 μg/kg) clonidine and in Group D (n = 30), 39 ml of 0.25% bupivacaine plus 1 ml (1 μg/kg) dexmedetomidine were given. The onset and duration of sensory and motor block, duration of analgesia, and quality of anesthesia were studied in both the groups. Results: There was no statistically significant difference in the onset of sensory and motor block in both the groups. The durations of sensory and motor block were 316.67 ± 45.21 and 372.67 ± 44.48 min, respectively, in Group C, whereas they were 502.67 ± 43.78 and 557.67 ± 38.83 min, respectively, in Group D. The duration of analgesia was 349.33 ± 42.91 min, significantly less in Group C compared to 525.33 ± 42.89 min in Group D (P < 0.001). The quality of anesthesia was significantly better in dexmedetomidine group compared to clonidine group (P < 0.001). Conclusion: The addition of dexmedetomidine prolongs the durations of sensory and motor block and duration of analgesia and improves the quality of anesthesia as compared with clonidine when injected with bupivacaine in supraclavicular brachial plexus block.